Pelatihan Pembuatan Modul Ajar Berbasis Chatgpt Sebagai Upaya Peningkatan Kompetensi Guru di MA Attarbiyah Addiniyah Al-Amin Gersik - Alfan Hadi; Samsul Hakim; Syamsul Hadi; Budiman (BALE LITERASI, 2026)
Teachers at MA Attarbiyah Addiniyah Al-Amin Gersik face difficulties in developing contextual and varied teaching modules that comply with the requirements of the Merdeka Curriculum, mainly due to limited time and low literacy in artificial intelligence technology (Fitriani, 2018; Fauzi & Wibowo, 2022). This community service program aimed to improve teachers' pedagogical and professional competence in developing teaching modules through the use of ChatGPT as an artificial-intelligence-based assistive tool. The implementation method consisted of four stages: preparation (needs analysis and coordination with the partner school), implementation (lectures, demonstrations, and guided practice in prompt writing), continued mentoring (independent practice supervised by the service team), and evaluation (pre-test, post-test, and observation of the resulting teaching module drafts). The program involved 24 teachers from various subjects. The results showed an improvement in teachers' understanding and skills in using ChatGPT to formulate learning outcomes, learning objectives, learning activities, and assessment instruments, as indicated by an increase in the mean pre-test to post-test scores and highly positive responses in the participant satisfaction questionnaire. Teachers were also able to produce teaching module drafts in significantly less time than the conventional process, consistent with the findings of Siboro et al. (2025) and Ahmad (2024). Challenges identified included the need for more mature prompt-writing literacy and the importance of independent editing to ensure that AI-generated content remains pedagogically sound and aligned with the madrasah's Islamic values. The program is concluded to be effective as a technology-based strategy for improving teacher competence and is recommended to be continued with further mentoring.